The importance of music for children with Autism Spectrum Disorder-ASD (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a developmental disorder that usually presents in early childhood. It is characterized by impairments in the ability to social interaction, communication skills and antisocial behaviors. In this way, the autistic child presents signs that can be perceived through observation with other children, especially with regard to social interaction. It is known that several resources can help these children, and, with that in mind, the present work aims to identify in the literature the importance of the use of music in the development of children with ASD. This is a research that presents itself with a social and scientific responsibility when thinking about children with ASD, making us think about the importance of music in the treatment of this disorder and the importance of studying it in the area of ​​education, in order to achieve better results when work with children who have the disorder. From the results, it was noticed that music is a great instrument for the development of children with ASD, because through it the child will break out of social isolation in order to favor their communication, expression and manifestation, stimulating it to obtain new ways of interacting.